Qi-Li-Qiang-Xin Alleviates Isoproterenol-Induced Myocardial Injury by Inhibiting Excessive Autophagy via Activating AKT/mTOR Pathway - Fan, Cailian; Tang, Xiyang; Ye, Mengnan; Zhu, Guonian; Dai, Yi; Yao, Zhihong; Yao, Xinsheng (Frontiers in Pharmacology, 2019)
Background: Apoptosis and autophagy are two important patterns of cell death in the process of heart failure. Qi-Li-Qiang-Xin (QLQX), a traditional Chinese medicine, has been frequently used in the treatment of chronic heart failure (CHF) in China. However, the potential effect of QLQX on autophagy has not been reported. In this study, we aimed to investigate whether QLQX alleviated isoproterenol (ISO)-induced myocardial injury through regulating autophagy. Methods: The rapid identification of chemical ingredients of QLQX was performed by UPLC-Q-TOF-MS, and the contents of major constituents in QLQX were also measured by UPLC-Q-TOF-MS. ISO was used to induce myocardial injury in H9c2 cardiomyocytes and SD rats. In vivo, cardiac function was evaluated by echocardiography and cardiac structure was observed by HE and Masson staining. Expressions of Bcl-2, Bax, LC3, P62, AKT, p-AKT, mTOR and p-mTOR were detected by western blotting. In vitro, H9c2 cells were pretreated with QLQX for 3 h before ISO (80 μM, 48h) addressed. Cell viability, LDH and CK-MB release, apoptosis ratio and the level of autophagy were measured. Western blotting was also performed to detected related protein expressions. Result：In vivo, treatment by QLQX significantly improved cardiac function and alleviated ISO-induced myocardial structural damage. In addition, QLQX markedly decreased apoptosis and inhibited autophagic activity, accompanied by activating the AKT/mTOR pathway. In vitro, the increased cell apoptosis induced by ISO was paralleling with the gradually increasing level of autophagy. Furthermore, 3-MA, an autophagic inhibitor, could block ISO-induced autophagy in H9c2 cells. Our results suggested that both QLQX and 3-MA treatment could decrease cell death induced by ISO, implying that QLQX protected against ISO-induced myocardial injury possibly by inhibiting excessive autophagy-mediated cell death. In addition, blockage of AKT signaling by an AKT inhibitor, capivasertib, could reduce the effect of QLQX on inhibiting ISO-induced apoptosis and autophagy-mediated cell death. Conclusion: QLQX could alleviate ISO-induced myocardial injury by inhibiting apoptosis and excessive autophagy-mediated cell death via activating the AKT/mTOR pathway.